Mathematical creativity in algebraic tasks of South African secondary school mathematics textbooks - Munyaradzi Chirove; Ugorji Ogbonnaya (Journal of Honai Math, 2026)
Fostering mathematical creativity is widely recognized as a fundamental objective of mathematics education because it enhances learners’ problem-solving capabilities and contributes to the achievement of Sustainable Development Goal 4 (Quality Education). However, limited empirical research has explored the extent to which mathematics textbooks support the development of mathematical creativity. This study examined how algebraic tasks in two South African secondary school mathematics textbook series promote mathematical creativity. Six textbooks were analyzed using quantitative content analysis, and independent samples t-tests were employed to determine whether significant differences existed between the textbook series. The analysis was guided by Ramelan and Wijaya’s framework of mathematical creativity, which comprises four dimensions: fluency, flexibility, elaboration, and originality. The findings revealed that the two textbook series fostered these dimensions to varying degrees. One series demonstrated a stronger emphasis on elaboration and originality, whereas the other provided greater support for fluency and flexibility. Overall, the textbooks moderately promoted fluency but offered limited opportunities for learners to develop flexibility, elaboration, and originality, suggesting that algebraic tasks generally provide insufficient support for the cultivation of mathematical creativity. Furthermore, the independent samples t-test indicated no statistically significant difference between the two textbook series in their overall promotion of mathematical creativity. These findings highlight a misalignment between curriculum aspirations and textbook implementation and underscore the need for richer, open-ended algebraic tasks that better support creative mathematical thinking.